Fabrication of chitosan/bioactive glass composite scaffolds for medical applications - Diana Marcela Escobar-Sierra; Johnnatan Stiven Posada-Carvajal; Diego León Atehortúa-Soto (Revista Facultad de Ingeniería Universidad de Antioquia, 2016)
In the current study, a bioactive glass (BG) powder was prepared by sol-gel technique in the system SiO2  –CaO–P2O5, and both, bioactive glass precursors (BGi) and the powder of bioactive glass (BGp) were used to produce crosslinked chitosan composite scaffolds (CH/BGi and CH/BGp), which were produced by lyophilization. The bioactive glass was analyzed to know its composition, crystallinity and morphology through Raman Spectroscopy (RS), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM), respectively. In addition, compression strength tests were carried out on the resulting composite scaffolds. Experimental results show that the fabricated CH/BG scaffolds might be a promising composite biomaterial for bone tissue engineering, due to the XRD results, showing a pollutant-free biomaterial, and, SEM shows bioactive glass particles homogenously distributed within the chitosan matrix which suggested that the developed composite scaffolds possess the prerequisites for tissue engineering and these can be used for tissue engineering applications.